The greatest show on Earth : the evidence for evolution - Dawkins, Richard, 1941- (Free Press, 2009)
Sifting through rich layers of scientific evidence, Dawkins' "The Greatest Show on Earth" is a stunning counterattack on advocates of "Intelligent Design," explaining the evidence for evolution while exposing the absurdities of the creationist "argument."- Resumé vydavatel
Keywords: evoluce (biologie); evoluční teorie; fylogeneze živočichů; biodiverzita; evolution (biology); evolutionary theories; animal phylogeny; biodiversity; elektronické knihy; populárně-naučné publikace; electronic books; popular works